Prevention of internalising disorders in 9-10 year old children: Efficacy of the Aussie optimism positive thinking skills program at 30-month follow-up - Rooney, Rosanna; Morrison, D.; Hassan, Sharinaz; Kane, Robert; Roberts, Clare; Mancini, V. (Frontiers Research Foundation, 2013)
The Aussie Optimism: Positive Thinking Skills Program (AOPTP) is a school based prevention program aimed at addressing anxious and depressive symptoms in children aged 9–10 years. Nine-hundred and ten students from 22 Australian primary schools situated in low socio-economic areas were randomly assigned to either an intervention or control group, and assessed at a 30-month follow up. Those in the intervention group received the AOPTP program, where the control group continued to receive the regular health education course. Students completed self-report measures regarding their levels of depression, anxiety, and attribution style. Parents also reported on their children’s externalizing and internalizing problems outside of school. There were no significant differences between groups in regard to anxiety or depression, as well as no significant differences in attributional styles. Parents reported significantly less hyperactive behaviors from children in the intervention group. This finding suggests that AOP-PTS has the capacity to treat externalizing problems at a medium term effect. The decrease in the externalizing problems provides evidence of a partial medium term intervention effect. Future studies should continue to evaluate the program at a long term follow up.